María Luisa Hernanz Carbó, El infinitivo en español. Universidad Autónoma de Barcelona, Bellaterra, 1982; 574 pp. - Schroten, Jan (Nueva Revista de Filología Hispánica (NRFH), 1984)
Se reseñó el libro: El infinitivo en español.